THE MEDIATING EFFECT OF PATIENT SATISFACTION ON THE RELATIONSHIP BETWEEN SERVICE QUALITY, HOSPITAL IMAGE, TRUST AND PATIENT LOYALTY: EVIDENCE FROM INDONESIA - Sefnedi., Akmal., & Nelva Sasmita (International Journal of Research Science and Management, 2020)
The development of healthcare industry in Indonesia has become very potential market and faced keen competition. One of marketing strategy to win the high competition is to createpatient satisfaction.The purpose of this study wasto examine the mediating effect patient satisfaction on the relationship between service quality, hospital image, patient trust and patient loyalty. The primary data for the study were collected from a selfadministered mail survey of 337 questionnaires from the hospital patients resulting in a sample of 214 usable responses being returned. The results showed that service quality and hospital image had significant effect on patient satisfaction and loyalty, while patient trust did not affect significantly patient satisfaction and loyalty. In addition, the variable of patient satisfaction was found to have positive effect on patient loyalty. Specifically, patient satisfaction mediated the relationship between service quality, hospital image and patient loyalty. However, it did not mediate the relationship between patient trust and patient loyalty